Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5194/acp-2019-971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxygen and sulfur mass-independent isotopic signatures in black crusts: the complementary negative ∆<sup>33</sup>S-reservoir of sulfate aerosols?

Abstract: <p><strong>Abstract.</strong> To better understand the formation and the oxidation pathways leading to gypsum-forming “black crusts” and investigate their bearing on the whole atmospheric SO<sub>2</sub> cycle, we measured the oxygen (δ<sup>17</sup>O, δ<sup>18</sup>O and ∆<sup>17</sup>O) and s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 55 publications
4
11
0
Order By: Relevance
“…The similarity between the isotopic values (especially the δ 34 S) from Sicilian black crusts (this study) and those from other cities in Europe (Longinelli & Bartelloni, 1978;Buzek & Šrámek, 1985;Pye & Schiavon, 1989;Torfs et al, 1997;Siedel, 2000;Klemm & Siedel, 2002;Přikryl et al, 2004;Vallet et al, 2006;Kloppmann et al, 2011;Genot et al, 2020) suggests that similar sulphur sources contribute to the formation of their black crusts. This study thus confirms that in large urban areas, the black crust formation mostly results from anthropogenic sulphur emissions (Winkler, 1966;Massey, 1999;Bugini et al, 2000;Cardell-Fernández et al, 2002;Charola & Ware, 2002;Lefèvre & Ausset, 2002;Holynska et al, 2004;Přikryl et al, 2004;Barca et al, 2011;Kramar et al, 2011;Farkas et al, 2018;La Russa et al, 2018;Genot et al, 2020). More interestingly, the present work broadens the study of black crusts to different and various atmospheric environments (urban, coastal, rural and volcanic areas), and show that anthropogenic emissions still J o u r n a l P r e -p r o o f Genot et al (2020).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…The similarity between the isotopic values (especially the δ 34 S) from Sicilian black crusts (this study) and those from other cities in Europe (Longinelli & Bartelloni, 1978;Buzek & Šrámek, 1985;Pye & Schiavon, 1989;Torfs et al, 1997;Siedel, 2000;Klemm & Siedel, 2002;Přikryl et al, 2004;Vallet et al, 2006;Kloppmann et al, 2011;Genot et al, 2020) suggests that similar sulphur sources contribute to the formation of their black crusts. This study thus confirms that in large urban areas, the black crust formation mostly results from anthropogenic sulphur emissions (Winkler, 1966;Massey, 1999;Bugini et al, 2000;Cardell-Fernández et al, 2002;Charola & Ware, 2002;Lefèvre & Ausset, 2002;Holynska et al, 2004;Přikryl et al, 2004;Barca et al, 2011;Kramar et al, 2011;Farkas et al, 2018;La Russa et al, 2018;Genot et al, 2020). More interestingly, the present work broadens the study of black crusts to different and various atmospheric environments (urban, coastal, rural and volcanic areas), and show that anthropogenic emissions still J o u r n a l P r e -p r o o f Genot et al (2020).…”
Section: Discussionsupporting
confidence: 63%
“…Following previous studies of natural sulphate-containing samples such as aerosols, rainwaters, ice cores or volcanic deposits Lee et al, 2001a;Romero et al, 2003;Jenkins et al, 2006;Mather et al, 2006;Sofen et al, 2011;Alexander et al, 2012;Martin, 2018). Genot et al (2020) reported recently on the first oxygen and sulphur multi-isotopic composition measurements of sulphate from black crust (δ 18 ) that are inherited from the ozone molecule precursor. When a sulphur gas (e.g.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations